A Direct Comparative Analysis of HPV DNA with Single-Molecule RNA and p16INK4a Protein Expression in Lichen Sclerosus: Implications for Diagnostics and Pathogenesis - Georgios Kravvas; Boyu Xie; Clarisse Ganier; Henk van den Munckhof; Ellen van den Munckhof; Maurits de Koning; Sandra Jerkovic Gulin; Alex Freeman; Aiman Haider; Hussain Alnajjar; Asif Muneer; Magnus Lynch; et al. (JID Innovations)
Introduction: Emerging evidence suggests a relationship between chronic, intermittent, occluded exposure of a susceptible epithelium to urine and male genital lichen sclerosus (MGLSc), although human papillomavirus (HPV) may also play a role. Aims and methods: This study investigated the association between MGLSc and HPV across the prepuce. Preputial samples from uncircumcised patients with MGLSc undergoing circumcision were tested for MGLSc distribution, HPV genotyping, RNAscope, and p16INK4a detection. Results: Preputial samples from 9 patients with MGLSc were analyzed, with 9 distinct areas per prepuce, yielding 81 samples. These included MGLSc, non-MGLSc, and indeterminate regions. Various mucosal and beta HPV types were detected, most commonly HPV24, HPV23, HPV36, and HPV9. HPV DNA was found in all patients, and high-risk HPV types were found in 6. No significant differences were observed in total HPV (P = .1) or oncogenic HPV (P = .6) between MGLSc and non-MGLSc tissues. Transcriptionally active HPV was absent in all samples on the basis of independent RNAscope and p16INK4a staining. Discussion: HPV DNA was detected in a mosaic pattern across the prepuce, with no significant differences between MGLSc and non-MGLSc skin. The absence of transcriptional activity suggests that HPV in MGLSc is incidental and may not contribute toward pathogenesis.